Blockchain Technology for IoT Security (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Internet of Things (IoT) promoted a common operating picture (COP) through all modern applications. The COP is takes place only accomplished by the developments seen in wireless sensor network devices that have been able to connect through the network, sharing information, and conducting further analysis. In IoT, knowledge sharing and authentication of data through the central server and is hence vulnerable to security and privacy problems. System spoofing, false authentication, less data sharing reliability may take place. As part of IoT, Blockchain (BC) technology is integrated to solve these security and privacy issues by replacing the idea of the central server. This paper discusses the potential protection and privacy threats of IoT component activity and explores how it relates to distributed ledger-based blockchain (DL-BC) technologies. . Blockchain implementations have explicitly been studied here with regard to focused sectors and categories. This paper also discusses Blockchain technology, its contribution, and challenges specific to IoT.